Vacancy-engineered catalysts for water electrolysis. Issue 9 (14th January 2020) - Choi, Songa; Park, Yeji; Yang, Heesu; Jin, Haneul; Tomboc, Gracita M.; Lee, Kwangyeol
Abstract : Vacancy-engineered electrocatalysts showing various effects on improving performances toward water electrolysis. Abstract : The development of electrochemical energy conversion and storage technologies is pivotal to the full-fledged utilization of renewable energy sources. The successful commercial application of water electrolysis to produce hydrogen gas, in particular, requires highly active electrocatalysts that can operate for prolonged periods. However, the high activity and high durability of electrocatalysts are often mutually exclusive. Recent studies have demonstrated that vacancy engineering might effectively modulate the electronic structures of catalysts, which can lead to high catalytic activity. Furthermore, it has been shown that vacancies are closely related to catalyst stability under operational conditions. To understand the benefits of vacancies in the catalyst structures, we discuss the recent advances in the development of vacancy-engineered catalysts for water electrolysis. In addition, we discuss the present limitations in this nascent field and provide directions for valuable future research.